2020
DOI: 10.1109/lgrs.2019.2916164
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Resolution in GNSS-R Under Coherent Scattering

Abstract: GNSS-R can be understood as a multi-static radar using satellite navigation signals as signals of opportunity. The scattered signals over sea ice, flooded areas-even under dense vegetation-, and in some cases over land show a significant coherent component. Under coherent scattering conditions, it is usually stated that the coherent signal component comes from an area equal to the first Fresnel zone. This work analyzes in more detail the spatial resolution in this forward scattering configuration, showing that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 15 publications
1
52
0
Order By: Relevance
“…From the analysis presented in Figure 7 it is observed that this occurs, on average, for rivers with a minimum width exceeding 250 m and 200 m for 1 Hz and 2 Hz CYGNSS data, respectively. This places a minimum bound on the finest spatial features CYGNSS measurements are able to resolve, on average, suggesting that this is on the order of a first Fresnel zone and provides empirical support for previous theoretical treatments of this question [23]. However, there are several caveats to this analysis which assumes that rivers will generally satisfy the conditions to produce coherent CYGNSS forward reflections:…”
Section: Analysis Of Coherent Surface Resolution Using Ancillary Rivesupporting
confidence: 64%
“…From the analysis presented in Figure 7 it is observed that this occurs, on average, for rivers with a minimum width exceeding 250 m and 200 m for 1 Hz and 2 Hz CYGNSS data, respectively. This places a minimum bound on the finest spatial features CYGNSS measurements are able to resolve, on average, suggesting that this is on the order of a first Fresnel zone and provides empirical support for previous theoretical treatments of this question [23]. However, there are several caveats to this analysis which assumes that rivers will generally satisfy the conditions to produce coherent CYGNSS forward reflections:…”
Section: Analysis Of Coherent Surface Resolution Using Ancillary Rivesupporting
confidence: 64%
“…The signal over land includes both coherent and incoherent scattering, with a relative weight that is subject to discussion [43,44]. The main observables related to the two mechanisms are the reflectivity and the Normalized Radar Cross Section, respectively.…”
Section: Satellite Data A) Cygnss Datamentioning
confidence: 99%
“…By mapping spatial changes in P cal , we can thus relate them to spatial changes in the surface reflectivity. Our dataset included GNSS-R reflections from the following PRNs: 3,7,8,9,11,14,16,22,23,26,27,28,30, and 31. Data were obtained from a range of incidence angles (min: 10.7 deg, max: 60 deg, mean: 34.7 deg).…”
Section: Caddo Lake Calibrated Datamentioning
confidence: 99%
“…It has been assumed that the received power from GNSS-R signals reflecting from water are coherent and follow the scattering model given by Equation 2 [11,23]. We attempted to verify this by selecting data over the open-water portions of Caddo Lake, which should show a relatively constant calibrated power level, and assessed whether P cal or P cal R 2 sr fit the data better.…”
Section: Scattering Modelmentioning
confidence: 99%